Chemical Constituents and Biological Activities of Glycosmis Chlorosperma Var. Elmeri (Merr.) Stone (Rutaceae) - Abdullah, Rosmiati; Rahmani, Mawardi; Manaf Ali, Abdul; Mohd Ismail, Hazar Bebe; Sukari, Mohd Aspollah; G.C.L, Ee; Kulip, ulius (Malaysian Journal of Science, 2006)
Detailed investigation on the leaves and barks of Glycosmis chlorosperma has led to the isolation and identification of a chalcone, dihydroglychalcone (1) and three sulphones - dambullin (2), sakambullin (3) and methylgerambullin (4), along with the common triterpene, stigmasterol. Compounds (1) (2) and (3) showed cytotoxic activity towards CEM-SS T-lymphoblastic cell lines. However, only dambullin (2) showed activity against pathogenic bacteria and fungi. We wish to report the isolation and bioassay results of the crude extracts and pure compounds.